A STUDY OF UNMANNED GLIDER DESIGN, SIMULATION, AND MANUFACTURING - Demircali, Anil; Uvet, Huseyin (CENTRAL BOHEMIA UNIV, 2017)
This paper describes a mini unmanned glider's design, simulation, and manufacturing with a wing-folding mechanism. The mini-glider is designed for the CANSAT 2016 competition, which has the theme of a Mars glider concept with atmosphere data acquisition. The aim is to facilitate transportation and to land it to the destination point. Having a light and compact design is important since it is a glider without an engine and it uses power only for the transmission of sensory data. The glider is produced with a wingspan which is 440 mm, and its longitudinal distance is 304 mm. The wings can be packaged in a fixed size container whose dimensions are 125 mm in diameter and 310 mm in height. The glider's weight is only 144 gr, and it can increase up to 500 gr with maximum with payload. The mechanism, which includes springs and neodymium magnets for wing-folding, is capable of being ready in 98 ms for gliding after separation from its container. The mini-glider is capable of telemetry, communications, and other sensory operations autonomously during flight.
Keywords: MAV; Autonomous System; Wing-Folding; Reconnaissance; Business & Economics; Public Administration